The Impact of Boys' Love Television Series as a Way of Shaping Thailand's LGBT Rights Acceptance - Hidayat, Addine Fithrianne (Institute of International Studies, 2024)
The journey of Thailand's cinematic queer existence can be traced back to the 1960s with a portrayal of a same-sex couple's tragic story. However, the re-emergence of Thailand's cinematic queer in the form of the Boys Live series in 2020 has succeeded in enticing audiences' attention and soon created the narrative of the exact sex couple series portrayal to be the icon of Thailand's entertainment industry. The increased demand for Boys Love series production later shifted into giving a proper platform for the LGBT community to represent themselves in the media. The expansion in exposure led to reshaping the discourse in society and creating a way for familiarising the community with the public, all while providing the chance to address the topic matters, including long-standing discrimination.Keywords: LGBT; human rights; discourse school; media representation; gender equality